(untitled) (Global Journal of Management and Business Research, 2022)
This study will help to compare both the restaurant of hotel in Radisson Blu, Kaushambi and understand about the services getting in the restaurant. It is very important to firstly understand the need to work on negative as well as positive guest experience because the hotel generates most of its revenue from different core operation area in which guest interaction is must, among them Restaurant plays major role in contributing guest satisfaction.